Clinical Observation on Children with Peripheral Facial Paralysis Treated by Acupoint Injection of Mouse Nerve Growth Factor Combined with Acupuncture - Mian KONG; Wei LIU; Zhihua YU; Ming FANG (康复学报, 2019)
Objective:To observe the clinical efficacy of acupoint injection of mouse nerve growth factor combined with acupuncture on peripheral facial paralysis children.Methods:A total of 89 peripheral facial paralysis children who met the diagnostic and inclusion criteria were randomly assigned to the observation group (n=45) and the control group (n=44). Both groups were treated with acupuncture treatment. Acupuncture points were selected according to syndrome differentiation based on symptoms of the children. Acupuncture therapy was conducted in a mild reinforcing-reducing method, once a day, six times per week and three weeks was considered as a treatment course. The observation group was given an extra acupoint injection of mouse nerve growth factor. Acupoints were selected on the affected side according to the symptoms of the child, including Tongziliao, Yingxiang, Chengjiang, etc.. Two acupoint were selected each time, three times a week, and these points were used alternately. After three weeks of treatment, the clinical efficacy, H-B facial nerve function grading, average effective time, Portmann score, compound muscle action potential (CMAP), nerve conduction velocity, blink reflex (BR) latency and adverse reactions were compared between the two groups.Results:Before treatment, there was no significant difference in H-B facial nerve function grading between the two groups (P> 0.05). After treatment, the improvement of H-B facial nerve function grading in the observation group was significantly better than that of the control group (P< 0.05). The average effective time in the observation group was less than that in the control group (P< 0.05). The difference of Portmann score in the observation group was greater than that in the control group (P< 0.05). Before treatment, there was no significant difference in CMAP amplitude, nerve conduction velocity and BR latency between the two groups (P> 0.05). After treatment, the CMAP amplitude, nerve conduction velocity and BR latency of the observation group were significantly higher than those of the control group (P< 0.05). The total effective rate of the observation group (91.11%) was significantly superior to that of the control group (75.00%) (P< 0.05). No serious adverse reactions occurred in this study. One case with local pain occurred in the observationgroup but without statistical difference (P> 0.05).Conclusion:The total effective rate of acupoint injection of mouse nerve growth factor combined with acupuncture in the treatment of children with peripheral facial paralysis is higher than that of acupuncture only, and the effective time is significantly shorter than that of acupuncture only. The improvement of H-B facial nerve function grading is significant, the average effective time is short, the difference of Portmann score is large, the CMAP amplitude is better, and the nerve conduction velocity is improved, and the postoperative adverse reaction is low, which could effectively improve the facial nerve of children, with quick response and high safety.